Shipyards in Egypt between antiquity, nowadays, and the future - Helmy, Aya Mohamed (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Shipyards in Egypt played an extensive role in building the Egyptian civilization through the ages. Significant archaeological excavations at several sites in Egypt revealed remains of shipyards dating back to antiquity. By studying shipyards in Egypt nowadays in different environments, the ethnographic research revealed the main features of the Egyptian shipyards and the industry of shipbuilding. Shipyards reflect both the materialistic aspect represented in tools and material, and the cultural aspect represented in labourers and builders; therefore, studying the Egyptian shipyards illustrates a lot of evidence about the future outlook of the shipbuilding industry in Egypt.